Utilización de cuentos infantiles para mejorar el nivel de autoestima de los niños y niñas de segundo y tercer grado de educación general básica, en la escuela fiscal mixta República de Cuba en la ciudad de Loja período lectivo 2013 – 2014 - Paqui González, Gicela del Cisne (2015)
The present titled thesis: USE OF INFANTILE STORIES to IMPROVE THE LEVEL OF SELF-ESTEEM OF THE CHILDREN AND GIRLS OF SECOND AND THIRD GRADE OF GENERAL BASIC EDUCATION, IN THE SCHOOL MIXED FISCAL REPUBLIC DE VAT IN THE CITY DE LOJA ACADEMIC YEAR 2013. 2014, he/she has as general objective: to determine the importance of the use of the infantile stories for the improvement of the level of the children's self-esteem and second girls and third grade of General Basic Education of the school mixed fiscal Republic Of Cuba of the city of Loja academic year 2013. 2014. To carry out this investigation the traverse and quasi- experimental design it was used, for their development it was used the methods: understanding, analytic, synthetic, participatory diagnosis, of models or proactive, of shop and the method of understanding evaluation; also, technical and instruments like: it interviews applied to an educational one and an observation guide with their respective questionnaire the same one that was applied to 11 second children and third grade of General Basic Education. After the analysis and interpretation of the obtained results, it has been determined the following deductions: The children and girls didn't know what is the self-esteem and at the same time they didn't have appropriate knowledge of what you/they are still the Infantile and worse Stories the importance that implies to apply them in the classroom, for such a reason in the application of Pre Test you evidences that the children presented a low self-esteem before applying the shops, such results you could verify thanks to the application from the survey to the children of the second and third grade of General Basic Education; when comparing the averages of the applied survey, using the coefficient Pearson, it was determined that the application of the Infantile" "Stories influences significantly as for the development of the self-esteem in the children and girls of the school mixed fiscal Republic of Cuba